Analysis of IPO underpricing and influencing factors in China's growth enterprise market - Yang, Huiru (2020)
IPO underpricing is a common phenomenon in various stock markets, and IPO underpricing is more prominent in China's GEM, which has a relatively short establishment period. Based on the combination of theoretical analysis and empirical research, this dissertation makes a comprehensive investigation of the underpricing of GEM in China, which has certain theoretical and practical significance for improving the financing efficiency of enterprises and improving the operating environment of the GEM market. This article uses the data of 782 listed companies listed on China's GEM from October 2009 to December 2019 as a sample and combines the characteristics of the GEM to select multiple factors that may affect the underpricing rate of the GEM. Through the use of statistical analysis, correlation test, and multiple regression linear models to investigate the influencing factors of underpricing. By dividing the sample into two periods, I find that the relationship between variables and IPO underpricing rate is different in different periods, and shows different significance. Finally, the paper concludes that investors' speculative psychology, ex-ante uncertainty, and underwriter reputation are the reasons for the high underpricing rate of GEM. Based on the above empirical results and analysis, the corresponding suggestions are put forward.